Revitalization of Winong Spring as a Generator of Ecotourism Activities to Promote Local Economic Development in Giripurno Village as One of Borobudur Buffer Zones - Junun Sartohadi; Ahmad Priyo Sambodo; Santika Purwitaningsih; Amir Noviyanto; Pramasti Dyah Nhindyasari; Dema Azmir Hatta; Marshanda Sasmita Putri; Hartanti Hartanti; Erika Galih Ayu Priyawati (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2023)
Establishing the National Tourism Strategic Area of Borobudur leaves challenges related to the surrounding villages. Most areas surrounding the Borobudur Temple, especially those in Menoreh Hills, have a high potential as a natural tourist destination. The main attractions are related to sightseeing and spring tourism. These potential attractions, however, have yet to be managed optimally due to the lack of resources of the surrounding villages, materially or socially. Our primary purpose is to reactivate the tourism potential in Giripurno Village by developing a new tourist attraction Winong Spring. We developed the new tourist attraction by structuring the current Winong Spring using lightweight, flexible, yet solid designs and building materials. We also revitalized abandoned fish ponds to become an integral Winong Spring tourist attraction feature. The tourist attraction developed at Winong Spring area becomes a new economic potential for Giripurno Village. The community receives the prospective tourist attraction of Winong Spring, which is also reflected in the high community participation in its development. It is also responding to the rising trending river tourism in Indonesia. Properly managed, the new prospective tourist attraction will benefit both ecosystem and economy. Thus, capacity building for tourism management and fish cultivation must be done. In addition, cohesive coordination from all stakeholders is required to guarantee the sustainability of the new potential tourist attraction.